A new record for the flora of Turkey: Eichhornia crassipes (Mart.) Solms (Pontederiaceae). (25th March 2014) - Uremis, I.; Uludag, A.; Arslan, Z. F.; Abaci, O.
Abstract : Eichhornia crassipes (Mart.) Solms (Pontederiaceae) is reported for the first time for the flora of Turkey. This invasive alien plant was observed in the Asi River (also called the Orontes River), which runs from Lebanon, through Syria to Turkey. The observation was made in the river near the border with Syria. This site is the in the district of Altinözü in the province of Hatay in the East Mediterranean region. Turkey is divided into grids for floral purposes by the book 'Flora of Turkey' and the plants described were collected in grid sector C6. The authors concluded that E .  crassipes (water hyacinth) can establish and spread in Turkey.